Citizen Science Illuminates a City-Dwelling Whale: A Report on the Large Aggregation of Narrow-Ridged Finless Porpoises in Tokyo Bay, Japan - Gen Nakamura; Ayumi Hirose (Fishes)
Tokyo Bay is one of the busiest ocean areas for human activity worldwide, characterized by a high density of maritime traffic and industrial development. This area is also recognized as the habitat of the narrow-ridged finless porpoise, an endangered toothed whale. Although the existence of this species has been recognized, its scientific data, such as population size and geographic distribution, are limited in the region. Therefore, using social media, we initiated a research project to collect sighting information on this species in Tokyo Bay. As a result, 27 valid pieces of information on the finless porpoises were collected from July 2024 to the end of February 2025. The sightings were reported mainly in the waters north of Futtsu Cape, indicating that this species is localized in the northern part of Tokyo Bay. Also, most of the reported sightings were of groups of wo or more animals. Notably, a school of at least 30 animals was recorded, marking the most prominent school ever observed in the region and the third largest in Japan. This study highlights the importance of the northern region of Tokyo Bay as a habitat for this species. The effective integration of citizen science with scientific and quantitative research will enhance our understanding of the life history of this endangered species, thereby supporting conservation efforts.